2020
DOI: 10.18231/2581-4729.2018.0056
|View full text |Cite
|
Sign up to set email alerts
|

Tinea genitalis in a rural tertiary care hospital of Western U.P. India

Abstract: Introduction: Genital dermatophytosis is also known as tinea genitalis and pubogenital tinea, and it is one of the superficial fungal infections caused by dermatophytes. The classical clinical presentations in an immunocompetent person consist of an erythematous annular plaque with slightly raised scaly centrifugally advancing border and central clearing. The lesions in patients with HIV/AIDS or immunosuppressed individuals, can be extensive and without central clearing.Purpose: The present study was conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…12 Divya et al reported that in combination Tinea corporis/Tinea cruris were more common which infected multiple sites (39%) followed by Tinea cruris (33%). 13 Thakur et al also stated the same that Tinea corporis (61.20%) was commonest clinical type followed by Tinea cruris (24.34%) and this fact was in agreement with the report of Doddamani et al 13,14 Sharma et al stated that the prevalence of Tinea corporis is reported high in many studies especially in India. Certain body parts are exposed more commonly than other body parts like the hand which can get in contact with another part which help the spread the infection.…”
Section: Discussionsupporting
confidence: 67%
“…12 Divya et al reported that in combination Tinea corporis/Tinea cruris were more common which infected multiple sites (39%) followed by Tinea cruris (33%). 13 Thakur et al also stated the same that Tinea corporis (61.20%) was commonest clinical type followed by Tinea cruris (24.34%) and this fact was in agreement with the report of Doddamani et al 13,14 Sharma et al stated that the prevalence of Tinea corporis is reported high in many studies especially in India. Certain body parts are exposed more commonly than other body parts like the hand which can get in contact with another part which help the spread the infection.…”
Section: Discussionsupporting
confidence: 67%
“…tinea faciei and tinea genitalis are being reported with increased frequency. [8][9][10][11][12] Corticosteroids misuse, usually topical, is the important contributing factor to this epidemic-like situation. 13…”
Section: Introductionmentioning
confidence: 99%
“…Dermatophytic infection of the pubo-genital region has been reported due to anthropophilic, zoophilic and geophilic dermatophytes [1][2][3][4][5][6][7] (Table 1). Previously, it invariably only used to be due to anthropophilic dermatophytes.…”
Section: Introductionmentioning
confidence: 99%
“…During the past 60 years, there has been a big change with predominance of zoophilic infections over anthropophilic infections. 14 Genital dermatophytosis has been found to be transmitted sexually, 1,2,6 by autoinoculation 4 and by excessive use of potent corticosteroids, topically or systemically. 5 In hot and humid climates, dermatophytosis is more common.…”
Section: Introductionmentioning
confidence: 99%